Intermittent collective dynamics of domain walls in the creep regime - Grassi, Matías Pablo (2018)
We study the ultraslow domain-wall motion in ferromagnetic thin films driven by a weak magnetic field. Using time-resolved magneto-optical Kerr effect microscopy, we access to the statistics of the intermittent thermally activated domain-wall jumps between deep metastable states. Our observations are consistent with the existence of creep avalanches: roughly independent clusters with broad size and ignition waiting-time distributions, each one composed by a large number of spatiotemporally correlated thermally activated elementary events. Moreover, we evidence that the large-scale geometry of domain walls is better described by depinning rather than equilibrium universal exponents.